Rapidly Progressive Myelopathy Caused by Aggressive Vertebral Hemangioma - Kevin A. Moattari; Rojeh Melikian; Sanjay K. Khurana (Case Reports in Orthopedics)
Introduction. Vertebral hemangiomas are the most common benign tumors of the spine, having an incidence of 10-12% in the general population. They are asymptomatic, incidental findings in the vast majority of patients; however, in rare cases, they can expand to cause neural compression. Aggressive lesions of this sort are most commonly found in the thoracic spine, and expansion leads to the subacute development of myelopathy. Case Report. The authors report a rare case of aggressive vertebral hemangioma at the T1 vertebral body which caused rapidly progressive myelopathy over the course of 7 days. Clinical and radiological findings are shown as well as surgical management of the lesion. The patient regained the ability to ambulate, and there was no evidence of disease recurrence at 2-year follow-up. Conclusions. Although aggressive vertebral hemangiomas are a rare cause of myelopathy, they must be kept in mind in the differential diagnosis of cord compressive lesions. In this case, contrary to most, the expansion of the hemangioma led to rapid development of neurological decline necessitating urgent surgical intervention.